2015
DOI: 10.1038/srep09121
|View full text |Cite
|
Sign up to set email alerts
|

Length Dependent Thermal Conductivity Measurements Yield Phonon Mean Free Path Spectra in Nanostructures

Abstract: Thermal conductivity measurements over variable lengths on nanostructures such as nanowires provide important information about the mean free paths (MFPs) of the phonons responsible for heat conduction. However, nearly all of these measurements have been interpreted using an average MFP even though phonons in many crystals possess a broad MFP spectrum. Here, we present a reconstruction method to obtain MFP spectra of nanostructures from variable-length thermal conductivity measurements. Using this method, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 45 publications
2
49
0
Order By: Relevance
“…The length of our system is shorter than the maximum phonon mean free path (PMFP) that has been predicted for Si–Ge nanowires with Monte Carlo simulations. The PMFP in Si–Ge nanowires span the range up to several micrometers (). Therefore, the contribution of long mean free path phonons is neglected in our setup and accordingly, the thermal conductivity is underestimated.…”
Section: Resultsmentioning
confidence: 99%
“…The length of our system is shorter than the maximum phonon mean free path (PMFP) that has been predicted for Si–Ge nanowires with Monte Carlo simulations. The PMFP in Si–Ge nanowires span the range up to several micrometers (). Therefore, the contribution of long mean free path phonons is neglected in our setup and accordingly, the thermal conductivity is underestimated.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the Eq. 2, one can find that for the L= , the k L = k ∞ /2, in this way, the EMFP corresponds to a length at which the system yields a thermal conductivity, half of the length independent thermal conductivity, k ∞ , 29,[64][65][66] . By fitting curves to the NEMD data points, the diffusive or in another word length independent phononic thermal conductivity of single-layer and free-standing C 3 N along the armchair and zigzag directions at room temperature are calculated to be 810±20 W/mK and 826±20 W/mK, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of size effects on the phonon thermal conductivity of crystalline thin films has been the topic of a wide array of studies [1][2][3][4] that have shaped the direction of fields rooted in nanoscale heat transfer and applications reliant on nanotechnology. It is well known that for films with thicknesses less than the length scale of their phonon mean free paths, thermal conductivity can be reduced due to incoherent boundary scattering of phonons ballistically traversing the film.…”
mentioning
confidence: 99%
“…The study of heat carrier mean free path contributions to thermal conductivity has evolved significantly over the past decade 13 through analytical methods like the thermal conductivity accumulation function 14 and experimental methods like Time Domain Thermoreflectance (TDTR) 15 and Broadband Frequency Domain Thermoreflectance (BB-FDTR) 16 . In the approach taken here, we use TDTR to measure the thermal conductivity of amorphous silicon films of varying thicknesses, an approach that Zhang et al 4 analytically demonstrated can provide information regarding the spectral dependence of the phonon thermal conductivity in nanosystems. While our results provide similar insight into the role of long mean free path propagons to the thermal conductivity of amorphous silicon as that reported by Liu et al 17 , our approach is fundamentally different.…”
mentioning
confidence: 99%